Wool Smuggling and the Royal Government in England, c.1337–63: Law Enforcement and the Moral Economy in the Late Middle Ages. (November 2022) - Raven, Matt
Abstract : The process of law enforcement helped to shape the state in the Middle Ages. This article uses an extensive array of court records to provide the first detailed account of royal efforts to police the illegal export of wool in mid-fourteenth century England, when the wool trade was subjected to unprecedented levels of taxation and discussed in moral, as well as fiscal, terms. It shows that these efforts remained heavily centralized in terms of both personnel and institutional form when many other areas of royal law enforcement were becoming increasingly devolved. The article then situates this centralized enforcement form within contemporary criticisms of royal taxation, the place of the royal courts in the wider legal geography of commercial regulation, and the localized dynamic underpinning many legal processes. It argues that the enforcement process was shaped and, indeed, blunted by a critical debate over the extent of royal power and its place within England's "moral economy." By situating the regulation of the wool trade in this series of regulatory and economic contexts at a particularly important moment in the development of the late medieval tax state, this article reveals wool smuggling to be a subject of wider significance to historians interested in the nature and—particularly—the limits of royal power and royal law in medieval England.